Complete chloroplast genome of Fraxinus griffithii C.B. Clarke (Oleaceae): Insights into genome structure and molecular phylogenetics (Bangladesh Journal of Plant Taxonomy, 2025)
This study deciphers the first complete chloroplast (Cp) genome of Fraxinus griffithii C.B. Clarke (Oleaceae), a medicinally important tree species native to Bangladesh, providing new insights into its genome structure and phylogenetic relationships. The circular Cp genome comprises a total length of 155,683 bp with a large single-copy region (86,466 bp), small single-copy region (17831 bp), and two inverted repeat regions (51,386 bp). The plastome encodes 130 genes, including 86 protein-coding genes, 36 transfer RNAs and eight ribosomal RNAs. Comparative genomic analysis revealed genome divergence, similar genomic architecture, and lack of large rearrangements within the Oleaceae family. The plastome harbored 46 simple sequence repeats (SSRs) and 49 longer repeats. Among the identified SSRs, mononucleotides (39) were the most frequent, while palindromic repeats predominated among the longer repeats. Nucleotide diversity analysis revealed rpl32 and ndhF genes of the SSC region as the most hypervariable DNA barcodes. Plastome-wide phylogeny supported the systematic position of F. griffithii within the subtribe Fraxininae of the tribe Oleeae. Molecular dating analysis suggests that F. griffithii originated approximately 15.07 million years ago, during the Langhian stage of the Middle Miocene epoch in the Neogene period of the Cenozoic era. The findings of this study provide the first Cp genome data for F. griffithii (GenBank Accession: PP669282.1), contributing to valuable insights into the evolutionary genomics of the family Oleaceae.Bangladesh J. Plant Taxon. 32(1): 27–44, 2025 (June)